Imunoexpressão das proteínas E-caderina, α-SMA, TGF-β e Snail em queilites actínicas e carcinoma epidermoide de lábio inferior - Morais, Hannah Gil de Farias (2021)
Epithelial-mesenchymal transition (EMT) is a biological process that has been widely studied in oral squamous cell carcinoma (SCC), however, it is still rarely evaluated in lip carcinogenesis. The aim of this study was to investigate the immunoexpression of E-cadherin, α-SMA, TGF-β and Snail proteins in actinic cheilitis (AC) histopathologically diagnosed as epithelial dysplasia, and in lower lip squamous cell carcinoma (LLSCC). The immunoexpression of E-cadherin, α-SMA, TGF-β and Snail was semiquantitatively analyzed in 54 cases of ACs and 49 LLSCCs. Aiming at association of immunohistochemical findings with clinicopathological variables and overall (OS) and disease-free (DFS) survival rates, cases were classified into low expression and high expression categories. There were no statistically significant associations with any of the proteins analyzed with the degree of severity of epithelial dysplasia in ACs (p > 0.05). Immunohistochemical analysis in LLSCCs revealed that low membrane expression of E-cadherin in tumor front was significantly associated with LLSCCs with ≥5 buds (p = 0.005) and high score for both BD model (p = 0.009) and the proposed model by Dourado et al. (2020) (p = 0.038), however, no significant associations were observed between immunoexpression of this protein and clinical parameters (p > 0.05). Significant associations were also found between low expression of α-SMA with LLSCCs in clinical stages TNM I/II (p = 0.05), low depth of invasion (p = 0.006), < 5 buds (p = 0.027) and score of low/intermediate risk, while high expression of this protein was associated with the outcome of death (p = 0.009). Significant associations were also found between α-SMA network/spindle immunostaining pattern with LLSCCs in TNM stages III/IV (p = 0.031), with high depth of invasion (p = 0.002), ≥5 buds (p = 0.027), high BD risk score (p = 0.001) and death outcome (p = 0.015). Regarding the TGF-β protein, statistically significant associations were noticed between its low expression in tumor buds with absence of lymph node metastasis (p = 0.047) and locoregional recurrence (p = 0.042), however, no significance was observed with any of morphological parameters (p > 0.05). Immunohistochemical analysis of Snail protein did not reveal any significant association with clinicopathological parameters (p > 0.05). The association analysis of protein immunoexpression between the lesions studied revealed significant results for a high cytoplasmic expression of E-cadherin and LLSCCs (p = 0.001), high expression of α-SMA and LLSCCs (p < 0.001), low expression of TGF -β and LLSCCs (p < 0.001) and high expression of Snail and ACs (p = 0.006). Survival analysis revealed a high expression of α-SMA in tumor front stroma (p = 0.013), a network immunostaining pattern of this protein (p = 0.046) and high expression of TGF-β in tumor buds (p = 0.043) were significantly associated with worse OS, and LLSCCs with high expression of α-SMA also had a higher risk of death (HR = 5.90, p = 0.030). High cytoplasmic expression of TGF-β in tumor buds was significantly associated with both worse DFS (p = 0.007) and higher risks of negative outcomes for DFS (HR = 4.44; p = 0.014). The results of present study suggest that although the immunoexpression of evaluated proteins does not indicate differences in degree of histopathological severity in ACs, dysregulations of these proteins were identified among the lesions studied. Furthermore, it was found that LLSCC with more aggressive behavior was associated with low expression of membrane E-cadherin, high expression of α-SMA and its network pattern, and low expression of TGF-β in tumor buds.